Errors in the Writing of Indonesian Sounds by Arabic Native Speakers Students at the University of Al Azhar, Cairo - Moh Masrukhi (Arabic Literature Department, 2022)
Learning Bahasa Indonesia (bI) for al-Azhar students is new knowledge. Indonesian language is considered a second language(L2) or third (L3) language after Arabic (Ar). Each of the languages being studied has its own system of rules. These differ significantly from one another on phonological, morphological, and syntactic levels. At the phonological level, for example, their mother tongue (B1), namely Arabic, does not have middle or middle cardinal vowels, does not have nasal sounds, such as (ə/elang), (ɛ/nènèk), (ng/datang) as in Indonesian language. This leads to errors and irregularities in the Indonesian language. Later issues include changes, omissions, and replacement of phonemes that should not be used in Indonesian vocabulary. Knowing which phonemes are a stumbling block and make the learning process difficult can help to prevent these defects from happening again. A number of research data were obtained from the results of reading and writing assignments for first semester students at Al-Azhar University, Faculty of Language and Translation in Cairo (FBT-UAC). Furthermore, the learners' changes, omissions, and replacement of phonemes in Indonesian sentences were classified using predetermined criteria. The obtained data were then analyzed using contrastive theory and error analysis. This theory is applied by comparing the phonemes used by learners with standard Indonesian phonemes. The results revealed that the errors that occurred were the emergence of vowel changes, consonant changes, phoneme omission, and the replacement of diphthongs with single phonemes. This error happens as a result of students' inadequate comprehension and lack of sufficient reading practice.